Beyond Sets : a Venture in Collection-Theoretic Revisionism. - Rescher, Nicholas; Grim, Patrick (Berlin : De Gruyter, 2011)
This book is the product of a collaboration stretching the years 2007-10, whose initial fruit was a paper on "Plenum Theory" published in Nous. The work grew out of the author's conviction that standard set theory, which had evolved to meet the needs of mathematics, was not fully adequate to the less abstractly geared and rigidly determine needs of less finalized ranges of inquiry and deliberation.
FOREWORD; Chapter One -- COLLECTIVITIES; Chapter Two -- MODES OF INDETERMINISTIC COLLECTIVITY; Chapter Three -- INDEXED INDETERMINACY AND VAGRANT COLLECTIVITIES; Chapter Four -- COLLECTIVITY THEORY: FIRST STEPS; Chapter Five -- PLENA; Chapter Six -- LOGICAL OPTIONS; Chapter Seven -- NUMBER BEYOND NUMBER; Name Index.
Print version record.
In English.
eBooks on EBSCOhost
Keywords: Set theory; Logic, Symbolic and mathematical; Théorie des ensembles; Logique symbolique et mathématique.; MATHEMATICS -- Set Theory; Logic, Symbolic and mathematical; Set theory